FDI and the Misery Index in Saint Lucia: Analyzing the Impact on a Tourism-Dependent Economy - Mangal, Tricia Karen Vernessa (International Journal of Economics and Financial Issues, 2025)
This study was conducted to examine the relationship that exists between Foreign Direct Investment (FDI) and the Misery Index (MI) in Saint Lucia. Moreover, other macroeconomic variables were included in order to understand their impact on FDI inflows into a small island developing economy. The research employs the Autoregressive Distributed Lag (ARDL) model to analyze the long-run and short-run relationships between FDI and the Misery Index. In addition, the study explores the influence of macroeconomic variables such as GDP per capita growth, trade openness, money supply, and total debt service on FDI inflows. Stationarity of the variables is confirmed using the Phillips-Perron (PP) and Augmented Dickey-Fuller (ADF) tests. It was found that there exists no significant long-run relationship between FDI and the Misery Index. However, GDP per capita growth, money supply, and total debt service, play a significant positive role in influencing FDI inflows. Moreover, there exists a negative relationship between trade openness and FDI. This relationship between trade openness and FDI can be attributed to Saint Lucia’s heavy reliance on tourism and not the trade- intensive sectors. In the short run, foreign direct investment has a negative relationship with money supply and the Misery Index. By examining the relationship between FDI and the Misery Index from the perspective of a small island developing state (SIDS) that is heavily dependent on tourism, this study contributes significantly to the existing literature.